Analisis Employee Engagement Dan Pelatihan Terhadap Kinerja Pegawai Melalui Komitmne Organisasional Sebagai Variabel Intervening Di RSUD Kota Mataram - Eka Safitri; Nizar Hamdi; Rosyia Wardani (Kredibel: Jurnal Ilmiah Manajemen, 2024)
The purpose of this research is to find out several things, namely: (1) the influence of employee engagement on organizational commitment, (2) the influence of training on organizational commitment, (3) the influence of employee engagement on employee performance, (4) the influence of training on employee performance, (5) the influence of organizational commitment on employee performance, (6) the influence of employee engagement on employee performance through organizational commitment, (7) the influence of training on employee performance through organizational commitment. The sample used was 92 employees of the Mataram City Regional Hospital. The data collection technique used in this research was a statement in the form of a questionnaire, using path regression analysis models 1 and 2. The results of this research show that: (1) employee engagement has a significant effect on organizational commitment because t count > t table, namely 3.093> 1.987, (2) training has a significant effect on organizational commitment because t count > t table, namely 4.084> 1.987, (3) employee engagement does not have a significant effect on employee performance because t count < t table, namely, 1,719<1,987, (4) training has a significant effect on employee performance because the t value>t table is, 4,952>1,987, (5) organizational commitment has an effect on employee performance because the t value>t table, namely 4,747>1,987, (6 ) employee engagement has a significant effect on employee performance through organizational commitment with a direct effect value of 0.142 which is greater than the in direct effect of 0.149, (7) training has no significant effect on employee performance through organizational commitment with a direct effect value of 0.381 with an in direct effect value of 0.156.